2014
DOI: 10.1109/tvcg.2013.103
|View full text |Cite
|
Sign up to set email alerts
|

Summarization-Based Image Resizing by Intelligent Object Carving

Abstract: Abstract-Image resizing can be more effectively achieved with a better understanding of image semantics. In this paper, similar patterns that exist in many real-world images are analyzed. By interactively detecting similar objects in an image, the image content can be summarized rather than simply distorted or cropped. This method enables the manipulation of image pixels or patches as well as semantic objects in the scene during image resizing process. Given the special nature of similar objects in a general i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…These are 4 basic principles of human visual attention. For saliency detection in the image, a multitude of methods which are explained in [19,20,21,22] can be used. In image and video compression the outcome of the saliency detection algorithm can be used [23].…”
Section: Salient Object Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are 4 basic principles of human visual attention. For saliency detection in the image, a multitude of methods which are explained in [19,20,21,22] can be used. In image and video compression the outcome of the saliency detection algorithm can be used [23].…”
Section: Salient Object Detectionmentioning
confidence: 99%
“…They also proposed a framework based on a multi-operator to integrate users' real visual preferences tightly. Dong et al [19] suggested a resizing method based on summarization. In this method, object carving is performed based on a multi-operator framework.…”
Section: Multi-operatormentioning
confidence: 99%